Permanent Carbon Dioxide Storage into Basalt: The CarbFix Pilot Project, Iceland - Matter, J.; Broecker, W.; Stute, M.; Gislason, S.; Oelkers, E.; Stefánsson, A.; Wolff-Boenisch, Domenik; Gunnlaugsson, E.; Axelsson, G.; Björnsson, G. (2009)
The storage of large volumes of industrial CO2 emissions in deep geological formations is one of the most promising climate mitigation options. The long-term retention time and environmental safety of the CO2 storage are defined by the interaction of the injected CO2 with the reservoir fluids and rocks. Finding a storage solution that is long lasting, thermodynamically stable and environmentally benign would be ideal. Storage of CO2 as solid magnesium or calcium carbonates in basaltic rocks may provide such a long-term and thermodynamically stable solution. Basaltic rocks, which primarily consist of magnesium and calcium silicate minerals, provide alkaline earth metals necessary to form solid carbonates. In nature, the carbonization of basaltic rocks occurs in several well-documented settings, such as in the deep ocean crust, through hydrothermal alteration and through surface weathering. The goal of the CarbFix pilot project is to optimize industrial methods for permanent storage of CO2 in basaltic rocks. The objective is to study the in-situ mineralization of CO2 and its long term fate. The project involves the capture and separation of flue gases at the Hellisheidi Geothermal Power Plant, the transportation and injection of the CO2 gas fully dissolved in water at elevated pressures at a depth between 400 and 800 m, as well as the monitoring and verification of the storage. A comprehensive reservoir characterization study is on-going prior to the CO2 injection, including soil CO2 flux measurements, geophysical survey and tracer injection tests. Results from the tracer tests show significant tracer dispersion within the target formation, suggesting large surface area for chemical reactions. The large available reservoir volume and surface area in combination with relatively rapid CO2-water-rock reactions in basaltic rocks may allow safe and permanent geologic storage of CO2 on a large scale. © 2009 Elsevier Ltd. All rights reserved.